2013
DOI: 10.1073/pnas.1313369110
|View full text |Cite
|
Sign up to set email alerts
|

Visible light alters yeast metabolic rhythms by inhibiting respiration

Abstract: Exposure of cells to visible light in nature or in fluorescence microscopy often is considered to be relatively innocuous. However, using the yeast respiratory oscillation (YRO) as a sensitive measurement of metabolism, we find that non-UV visible light has a significant impact on yeast metabolism. Blue/green wavelengths of visible light shorten the period and dampen the amplitude of the YRO, which is an ultradian rhythm of cell metabolism and transcription. The wavelengths of light that have the greatest effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 45 publications
1
69
0
Order By: Relevance
“…Alternatively, the Cry2 and Cib1 proteins from plants dimerize in the presence of blue light, which can in turn be used to activate a modified bacterial lexA promoter (28,34). And although we have previously shown that intense visible light perturbs the yeast oscillation, we have also shown that intensities less than 100 E/m 2 /s have little effect on the oscillation (9). A lightinducible promoter system offers the advantages of a heterologous gene control system that can be rapidly activated or inactivated without adding chemicals to the culture or disturbing the oscillation.…”
Section: Figmentioning
confidence: 71%
See 1 more Smart Citation
“…Alternatively, the Cry2 and Cib1 proteins from plants dimerize in the presence of blue light, which can in turn be used to activate a modified bacterial lexA promoter (28,34). And although we have previously shown that intense visible light perturbs the yeast oscillation, we have also shown that intensities less than 100 E/m 2 /s have little effect on the oscillation (9). A lightinducible promoter system offers the advantages of a heterologous gene control system that can be rapidly activated or inactivated without adding chemicals to the culture or disturbing the oscillation.…”
Section: Figmentioning
confidence: 71%
“…Rhythmic production of proteins from oscillating cultures can be more efficient than steady-state production, especially for unstable proteins and those strongly affected by cell cycle-dependent proteases (5,6). A respiratory oscillation manifests in yeast under specific conditions of continuous culture and exhibits 1-to 6-h rhythms of oxygen consumption, cell division, metabolite production, and gene expression (7)(8)(9)(10), all of which may make certain phases of the oscillation better for rhythmic protein production than others.…”
mentioning
confidence: 99%
“…The growth of yeast strains that are null for the yeast activator protein-1 gene that regulates oxidative stress genes is exquisitely sensitive to visible light. This reveals that light can both modulate respiration and induce oxidative stress [7].…”
Section: Plants and Animalsmentioning
confidence: 94%
“…Some researchers have proposed that high-frequency metabolic feedback loops—under selective pressure from the daily environment—were recruited to coalescence of an approximately daily period (16). Another model for the evolution of circadian timing—the so-called escape-from light hypothesis (7, 143, 144)—posits that light can damage cellular metabolism (e.g., DNA damage caused by UV light), which could have been a selective force for the evolution of circadian pacemakers. Briefly, the escape-from-light hypothesis proposes that light during the sunlit portion of the daily cycle had profound and mostly deleterious effects on early life; therefore, phasing cellular processes that are hypersensitive to light so that they occur in the dark nighttime may have driven the early evolution of circadian timers.…”
Section: Evolution Of Circadian Systems: Did Metabolic Cycles Play a mentioning
confidence: 99%
“…The authors of this paper suggested that most organisms that survived the transition to an aerobic environment 2.5 billion years ago were those that respired and/or evolved oxygen. Electron-transport chains involving oxygen inevitably produce ROS by-products, and due to daily cycles of photosynthesis and metabolism driven by daily LD and temperature changes, these ROS were produced rhythmically over the span of the daily cycle (113, 144). Therefore, a system to anticipate and manage the concomitant daily generation of intracellular ROS was adaptive.…”
Section: Evolution Of Circadian Systems: Did Metabolic Cycles Play a mentioning
confidence: 99%